ANALISA GAMBARAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA RUMAH TANGGA DI RT 027 RW 012 DESA MAMPIR KEC. CILEUNGSI BOGOR - Desi Ikaristi; Rokhaidah (AKPER Pasar Rebo, 2018)
Clean and Healthy Life Behavior (CHLB) is essentially a preventive behavior by individuals or families of various diseases. This study aims to determine the description of CHLB in households. The research design used in this study is descriptive analytical quantitative research. This research was conducted on 50 respondents, namely the head of a family member in RT 027 RW 012 Mampir Village, Cilaungsi District, Bogor. The results of this study get results; maternal pritas status has ever been pregnant (92.0%); childbirth assistance by midwives (60.0%) and delivery assisted by doctors (32.0%); mothers give exclusive breastfeeding (78.0%); mothers always weigh babies every month (80.0%): the condition of clean water without dirt (94.0%); maternal compliance with hand washing (100.0%); conditions of latrines with healthy latrine conditions (100.0%); routinely eradicate mosquito larvae (82.0%); always consume fruits and vegetables every day (70.0%); always doing physical activities (24.0); family members who smoke inside the house (68.0%) .The conclusions of the results of this study are for indicators of fruit and vegetable consumption, physical activity and non-smoking in the home still need to be improved.